2009
DOI: 10.1111/j.1365-2745.2009.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil biota accelerate decomposition in high‐elevation forests by specializing in the breakdown of litter produced by the plant species above them

Abstract: Summary1. There is mounting evidence that leaf litter typically decomposes more rapidly beneath the plant species it derived from than beneath the different plant species, which has been called home-field advantage (HFA). It has been suggested that this HFA results from the local adaptation of soil communities to decompose the litter that they encounter most often, which probably comes from the plant species above them. 2. To test this hypothesis and to investigate how HFA varies over time and in relation to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
160
5
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 60 publications
7
160
5
5
Order By: Relevance
“…But contrary to what could be expected, Ayres et al (2009c) found that litter decomposes more rapidly near the plant that produces it. This is probably the result of specialization by decomposers.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…But contrary to what could be expected, Ayres et al (2009c) found that litter decomposes more rapidly near the plant that produces it. This is probably the result of specialization by decomposers.…”
contrasting
confidence: 51%
“…The vegetation that is chosen in a restoration program will define temperature and soil humidity, mainly due to canopy density, stratus structure, sunlight that can reach understory and soil, leaf litter production and decomposition rate, and tree falling rate, among others (Mosquera et al 2007). It also defines: soil physical and chemical properties (Ayres et al 2009a); understory plant species composition; litter composition coming from the canopy and understory; leaf litter nutrients, production and decaying rate (Mosquera et al 2007, Scherer-Lorenzen et al 2007, Hättenschwiler et al 2008, Vivanco & Austin 2008; organism diversity (Vasconcelos 1999, Naranjo-García 2003, Doblas 2007, Sán-chez et al 2007, Bonilla et al 2008, CastroDíez et al 2008, Ayres et al 2009c; and forest regeneration and recovery rates and patterns (Letcher & Chadzon 2009). It has been shown, that the replacement of native by exotic species affects the litter production rate, nitrogen content and nutrient release during decomposition (Bonilla et al 2008, Castro-Díez et al 2008.…”
mentioning
confidence: 99%
“…Carbon (C) release from foliar litter is a primary component in C exchange among the atmosphere, vegetation, soil and water from respiration and leaching (Berg and McClaugherty, 2008), in that the majority of fixed C enters decomposition pathways (Cebrian, 1999;Ayres et al, 2009). Climatic controls on litter decomposition have gained considerable interest in recent years on account of accumulative green house gas feedback data from ecosystems Fraser and Hockin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the history of any one habitat might shape microbial community function under a new resource environment. To test for such historical effects one can compare ecosystem process rates in a common environment, inoculated with microbial communities sourced from different environments (Ayres et al, 2009;Langenheder and Prosser, 2008;Reed and Martiny, 2007;Strickland et al, 2009a). Using this approach, Strickland et al (2009a) demonstrated that resource history generated functionally dissimilar communities, with history explaining between 22 and 86 % of variance in the ecosystem process measured.…”
Section: Introductionmentioning
confidence: 99%